2020
DOI: 10.3390/dairy1020011
|View full text |Cite
|
Sign up to set email alerts
|

The Biosorption Capacity of Saccharomyces Cerevisiae for Cadmium in Milk

Abstract: This study aimed to evaluate the capacity of Saccharomyces cerevisiae for Cadmium absorption in milk. Nowadays, one of the most serious problems of the industrialized world is heavy metal pollution. Applying microorganisms as novel biotechnology is very useful, especially in foodstuffs. Among the biosorbents used for heavy metal removal, Saccharomyces cerevisiae has received increasing attention due to its popularity in the food industry. In this regard, the effects of some important factors such as the initia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…Due to its dangerous potential to human life and the environment, there is a growing requirement for simultaneous monitoring of metals, such as Hg, Pb, As, and Cd in water samples ( CONAMA, 2005 ; Mello et al., 2005 ). In previous reports of our research team, we studied the potential of yeast for biosorption of metals from food at low concentrations (ppb) from water and milk ( Hadiani et al., 2018a , Hadiani et al., 2018b ; Hadiani et al., 2019 ; Massoud et al., 2020 , 2021 ). But there are a few studies on the ability of S. cerevisiae to remove low concentrations of Hg, Pb, As, and Cd in multi-metallic solutions and subsequent assessment of the bond stability of S. cerevisiae and heavy metals (simultaneous presence of these four metals in liquid phase) in simulated gastrointestinal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its dangerous potential to human life and the environment, there is a growing requirement for simultaneous monitoring of metals, such as Hg, Pb, As, and Cd in water samples ( CONAMA, 2005 ; Mello et al., 2005 ). In previous reports of our research team, we studied the potential of yeast for biosorption of metals from food at low concentrations (ppb) from water and milk ( Hadiani et al., 2018a , Hadiani et al., 2018b ; Hadiani et al., 2019 ; Massoud et al., 2020 , 2021 ). But there are a few studies on the ability of S. cerevisiae to remove low concentrations of Hg, Pb, As, and Cd in multi-metallic solutions and subsequent assessment of the bond stability of S. cerevisiae and heavy metals (simultaneous presence of these four metals in liquid phase) in simulated gastrointestinal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Biosorption with Saccharomyces Cerevisiae allowed the removal of 70% of lead, mercury, and cadmium metals. 230,[233][234][235] The removal percentage was higher when Lactobacillus Acidophilus was used, eliminating 80, 75, and 72%, respectively. 231,232 The use of Saccharomyces cerevisiae and Lactobacillus helveticus removed AFM1 from milk by an as yet unknown binding mechanism.…”
Section: Alternative Methods For the Treatment Of Cow's Milkmentioning
confidence: 97%
“…They concluded that optimized conditions for lead removal were obtained after 4 days (at the end of storage time) with the content of 22×10 8 CFU/mL of yeast and 70 μg/L of lead in milk (Massoud et al, 2019). Similarly, the optimized process for cadmium bioremoval was achieved after 4 days with 80 μg/L of cadmium and 30×10 8 CFU/mL of S. cerevisiae Biodecontamination of milk and dairy products (Massoud et al, 2020a). Therefore, they have introduced applying S. cerevisiae as a novel and useful technology for the bioremoval of heavy metals from foodstuff (Massoud et al, 2019(Massoud et al, , 2020a Different treatments, such as caustic, ethanol, acidic, and heat, can enhance the biosorption of heavy metals by microorganisms.…”
Section: Heavy Metals' Bioremoval In Milk and Dairy Productsmentioning
confidence: 99%
“…In two different studies by Massoud et al (2019Massoud et al ( , 2020a, application of S. cerevisiae to reduce the concentrations of lead and cadmium in milk was examined. The optimization process was also performed considering three factors including contact time, concentrations of biomass, and initial content of heavy metals (Massoud et al, 2019(Massoud et al, , 2020a. Generally, the rate of removal of heavy metals increased with an increase in the biomass, contact time, and concentration of heavy metals.…”
Section: Heavy Metals' Bioremoval In Milk and Dairy Productsmentioning
confidence: 99%
See 1 more Smart Citation